A Study On The Consumer Behavioural Intention Among Customers Of McDonalds And Kentucky Fried Chicken(A Study On The Fast Food Industry Of Nilai) - Cheng, Yap Tiong (2003)
This study looks at the factors influencing consumer behavioural intention among customers of McDonalds and kentucky Fried Chicken in Nilai. This is done based on Lee's modified Fishbein model, which incorporates two salient Confucian concepts - face savi